The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ppc.12555
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between COVID‐19 knowledge levels and anxiety states of midwifery students during the outbreak: A cross‐sectional web‐based survey

Abstract: Purpose: To determine the relationship between the anxiety states and knowledge levels of female midwifery students about COVID-19 during the outbreak. Design and Methods: This cross-sectional study carried out with online participation of 972 female midwifery students. Findings: The anxiety levels of the female midwifery students were high among those visiting the hospital during the pandemic and having parents or relatives who had chronic diseases. Female midwifery students had a high level of knowledge rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
86
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 33 publications
17
86
5
3
Order By: Relevance
“…Students from MBBS and BDS stream were aware of facts like the causative factors for the COVID-19 disease (95.6%) and the type of virus causing this infection (92.7%). This was in accordance with a recent study from Turkey and Pakistan [17,21], where majority of students, (97.4%) were aware about the causes and the viral nature of the disease and also with another study from India, which showed 92.7% of the participants' had good knowledge. [22] Our study showed that only 71% of students were aware about the mode of transmission of this virus, which is lesser compared to a similar study from India among students, where 91% knew about the transmission modes and the signs and symptoms of the disease.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Students from MBBS and BDS stream were aware of facts like the causative factors for the COVID-19 disease (95.6%) and the type of virus causing this infection (92.7%). This was in accordance with a recent study from Turkey and Pakistan [17,21], where majority of students, (97.4%) were aware about the causes and the viral nature of the disease and also with another study from India, which showed 92.7% of the participants' had good knowledge. [22] Our study showed that only 71% of students were aware about the mode of transmission of this virus, which is lesser compared to a similar study from India among students, where 91% knew about the transmission modes and the signs and symptoms of the disease.…”
Section: Resultssupporting
confidence: 91%
“…Another study from Jordan showed a high knowledge of more than 80% and a Turkish study revealed a higher knowledge levels in female midwifery students compared to the present one. [17,18] The areas where the participants were having lesser knowledge were on PPE and facilities for proper management of COVID-19 at health facilities. In today's circumstances when there is high demand of PPEs, health science students must have correct knowledge on types of PPEs recommended at various work stations at health facilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has already been shown in medical staff facing previous health crises, where perceived sufficiency of information about the A/H1N1 influenza prognosis was independently associated with reduced degree of worry [ 42 ]. While the correlation of COVID-19 knowledge and anxiety did not reach statistical significance in another study conducted on midwifery students [ 43 ], it showed contribution to lowering perceived levels of stress, which do correlate with anxiety [ 26 ]. This reinforces how timely and transparent information, which is critical for healthy psychological self-adaptation regarding fast onset emergencies [ 3 ], might not have been accurately delivered to the general population, who could have been more exposed to sensational misinforming news reports in unofficial channels, whereas medicine students could have been prematurely aware of a belated official information disclosure [ 3 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on mental health during the pandemic among Turkish [43], medical [54], nursing [55,56], and midwifery [57] students, although less attention is given to non-medical students' mental health.…”
Section: Introductionmentioning
confidence: 99%